Comportamento hidromecânico de solos reforçados com fibras considerando a condição não saturada - Castro, Cíntia Lopes de (2020)
Soil reinforcement by adding polypropylene fibers can be a good alternative to solve geotechnical problems, as it tends to increase soil resistance in relation to natural condition. However, in the literature there are few studies that investigate the behavior of soils reinforced with fibers in the unsaturated condition. In view of this, the present work aims to study the stress-deformation behavior of soil-fiber mixtures, considering the unsaturated condition. As a stage of this research, an experimental program was developed in the laboratory, which consisted of the performance of geotechnical and mineralogical characterization tests of soil and soil-fiber mixtures, in addition to hydromechanical characterization. Polypropylene fibers with a length of 6mm and 18°m in diameter were used. The unsaturated condition was analyzed through soil retention curves and soil-fiber mixtures obtained by performing filter paper tests for fiber contents of 0, 0.25, 0.5, 0.75, 1.0 and 1.25% in relation to dry soil weight, in order to obtain the relationship of suction with soil moisture. The results allowed identifying the transition from the format of the unimodal to bimodal retention curves, caused by the inclusion of polypropylene fibers, suggesting the modification of the hydromechanical characteristics with the addition of reinforcement. In addition, a comparative analysis of the stress-deformation-resistance was performed in saturated and unsaturated conditions, with the performance of triaxial CID assays for fiber contents of 0, 0.25, 0.75 and 1.25% in relation to dry soil weight. The results of triaxial compression assays in the saturated condition demonstrated an increase in resistance with the inclusion of fibers, mainly for higher fiber contents. Regarding the results in the unsaturated condition, it was verified that the unsaturated resistance of the reinforced soil is altered, observing an increase in the cohesive intercept with the addition of fibers to the soil and with the decrease in saturation.